Interfacial region of poly(n‐butyl acrylate)/silicon oxide. Issue 16 (9th November 2020) - Matsuura, Kazuki; Kuboyama, Keiichi; Ougizawa, Toshiaki
Abstract: Poly( n ‐butyl acrylate) (PnBA) and silica nanoparticle composites were cast from toluene solutions and investigated via differential scanning calorimetry (DSC), Fourier‐transform infrared spectroscopy (FT‐IR), and X‐ray diffraction (XRD) analysis. The results suggested that the composites contained amorphous bulk and interfacial regions. The mobility of side chains at the interfaces between PnBA and the silica nanoparticles differed from the mobility of side chains in bulk PnBA. FT‐IR analysis showed that the difference in mobility was due to interactions between the carbonyl groups in PnBA and the silica surfaces. These results indicated that PnBA main chains near interfaces with silicon oxide were separated by a smaller distance than main chains in the bulk polymer. Abstract : Physical properties of polymer side interfacial region in polymer/inorganic nanoparticle composite are different from those of bulk region. The effect of interaction between poly( n ‐butyl acrylate) (PnBA) and silicon oxide was investigated via X‐ray diffraction (XRD). XRD patterns show that PnBA has a smaller space between its main chains in the interfacial region. We find that PnBA has the interfacial region with lower mobility than the bulk region.